Blockade of Store-Operated Calcium Entry Reduces IL-17/TNF Cytokine-Induced Inflammatory Response in Human Myoblasts - Beringer, Audrey; Gouriou, Yves; Lavocat, Fabien; Ovize, Michel; Miossec, Pierre (Frontiers in Immunology, 2019)
Muscle inflammation as in idiopathic inflammatory myopathies (IIM) leads to muscle weakness, mononuclear cell infiltration and myofiber dysfunction affecting calcium channels. The effects of interleukin-17A (IL-17) and tumor necrosis factor-α (TNFα) on inflammation and calcium changes were investigated in human myoblasts. Human myoblasts were exposed to IL-17 and/or TNFα with/without store-operated Ca2+ entry (SOCE) inhibitors (2-ABP or BTP2). For co-cultures, peripheral blood mononuclear cells (PBMC) from healthy donors activated or not with phytohemagglutinin (PHA) were added to myoblasts at a 5:1 ratio. IL-17 and TNFα induced in synergy CCL20 and IL-6 production by myoblasts (>14-fold). PBMC-myoblast co-cultures enhanced CCL20 and IL-6 production in the presence or not of PHA compared to PBMC or myoblast monocultures. Anti-IL-17 and/or anti-TNFα decreased the production of IL-6 in co-cultures (p<0.05). Transwell system that prevents direct cell-cell contact reduced CCL20 (p<0.01) but not IL-6 secretion. IL-17 and/or TNFα increased the level of the ER stress marker Grp78, mitochondrial ROS and promoted SOCE activation by 2-fold (p<0.01) in isolated myoblasts. SOCE inhibitors reduced IL-6 production induced by IL-17/TNFα. IL-17 and TNFα increased massively inflammatory cytokine secretion and induced ER stress, mitochondrial ROS and SOCE activation. SOCE contributed to inflammation since its inhibition reduced IL-6 release induced by IL-17/TNFα. Therefore, muscle inflammation induced by IL-17 and/or TNFα increased muscle cell dysfunction, which in turn increased inflammation.